Bibliometric Analysis of the Inflammasome and Pyroptosis in Brain - Chen, Yuhua; Li, Yan; Guo, Limin; Hong, Jun; Zhao, Wenjuan; Hu, Ximin; Chang, Cuicui; Liu, Wei; Xiong, Kun (Frontiers in Pharmacology, 2021)
Background: Considering the pivotal role of inflammasome/pyroptosis in biological function, we visually analyzed the research hotspots of inflammasome/pyroptosis related to the brain in this work through the method of bibliometrics from the Web of Science (WOS) Core database over the past two decades. Methods: Documents were retrieved from WOS Core Collection on October 16, 2020. The search terms and strategies used for the WOS database are as follow: # 1, “pyroptosis”; # 2, “pyroptotic”; # 3, “inflammasome”; # 4, “pyroptosome”; # 5 “brain”; # 6, “# 1” OR “# 2” OR “# 3” OR “# 4”; # 7, “# 5” AND “# 6”. We selected articles and reviews published in English from 2000 to 2020. Visualization analysis and statistical analysis were performed by VOSviewer 1.6.15 and CiteSpace 5.7. R2. Results: 1,222 documents were selected for analysis. In the approximately 20 years since the pyroptosis was first presented, the publications regarding the inflammasome and pyroptosis in brain were presented since 2005. The number of annual publications increased gradually over a decade, which are involved in this work, and will continue to increase in 2020. The most prolific country was China with 523 documents but the United States was with 16,328 citations. The most influential author was Juan Pablo de Rivero Vaccari with 27 documents who worked at the University of Miami. The bibliometric analysis showed that inflammasome/pyroptosis involved a variety of brain cell types (microglia, astrocyte, neuron, etc.), physiological processes, ER stress, mitochondrial function, oxidative stress, and disease (traumatic brain injuries, stroke, Alzheimer’s disease, and Parkinson’s disease). Conclusion: The research of inflammasome/pyroptosis in brain will continue to be the hotspot. We recommend investigating the mechanism of mitochondrial molecules involved in the complex crosstalk of pyroptosis and regulated cell deaths (RCDs) in brain glial cells, which will facilitate the development of effective therapeutic strategies targeting inflammasome/pyroptosis and large-scale clinical trials. Thus, this study presents the trend and characteristic of inflammasome/pyroptosis in brain, which provided a helpful bibliometric analysis for researchers to further studies.